2016
DOI: 10.1111/jpet.12192
|View full text |Cite
|
Sign up to set email alerts
|

Taxing the Financially Integrated Multinational Firm

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Third, we implicitly assume that the size of the corporate tax gap is the sole motivation behind corporate profit shifting, but this may not always be the case. Although there is strong evidence that corporate tax rate differences affect the geographical distribution of profits of multinational corporations, Johannesen (2016) observed that internal loans of German firms often flowed from high-tax countries to low-tax countries, which would not be expected if profit shifting to save tax was the only driving factor behind the loans. Profit shifting is also not the only method to reduce corporate tax.…”
Section: Discussionmentioning
confidence: 96%
“…Third, we implicitly assume that the size of the corporate tax gap is the sole motivation behind corporate profit shifting, but this may not always be the case. Although there is strong evidence that corporate tax rate differences affect the geographical distribution of profits of multinational corporations, Johannesen (2016) observed that internal loans of German firms often flowed from high-tax countries to low-tax countries, which would not be expected if profit shifting to save tax was the only driving factor behind the loans. Profit shifting is also not the only method to reduce corporate tax.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding specific BEPS actions, Johannesen () studies tax avoidance with debt financing. Behrens, Peralt, and Picard () examine transfer pricing regulation.…”
mentioning
confidence: 99%
“…Recently, Johannesen () finds an alternative explanation for the fact that most countries levy corporate taxes at fairly high rates. In the presence of multinational firms that finance investment in one country with loans from affiliates in another country, the burden of the corporate taxes levied in the latter partly falls on investment and thus workers in the former.…”
mentioning
confidence: 99%